2017
DOI: 10.20964/2017.04.09
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Graphene/Polythiophene (GR/PT) Nanocomposites: Evaluation as High-Performance Supercapacitor Electrodes

Abstract: Composites of polythiophene (PT) and graphene (GR) with different mass proportions were studied for their application as supercapacitors. Fourier transform infrared spectroscopy (FTIR) along with High Resolution Scanning electron microscopy (HR-SEM) were employed in order to characterize the morphology and composition of the resulting composites. The electrochemical behaviour of these composites was studied by means of cyclic voltammetry and specific capacitance curves were derived from these measurements. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 61 publications
3
14
0
Order By: Relevance
“…Furthermore, it was also shown that the capacitive property of MnO 2poly(o-aminophenol) is higher relative to the poly(o-aminophenol), and the composite was used as a promising material in supercapacitors. Melo et al [225] reported the preparation of the graphene/polythiophene (GR/PT) composite via the spray coating technique. The composite exhibited a higher specific capacitance of (365 F/g at 1 A g −1 ) relative to the single components and employed as electrode material in supercapacitors.…”
Section: Functionalization With Polymersmentioning
confidence: 99%
“…Furthermore, it was also shown that the capacitive property of MnO 2poly(o-aminophenol) is higher relative to the poly(o-aminophenol), and the composite was used as a promising material in supercapacitors. Melo et al [225] reported the preparation of the graphene/polythiophene (GR/PT) composite via the spray coating technique. The composite exhibited a higher specific capacitance of (365 F/g at 1 A g −1 ) relative to the single components and employed as electrode material in supercapacitors.…”
Section: Functionalization With Polymersmentioning
confidence: 99%
“…For the CV curves of pristine P3HT shown in Fig. 5 a, the current increases with scan rate and maintains the shape of CV curves, suggesting that there is a good rate of the capability 43 .
Figure 5 ( a ) CV curves of P3HT at different scan rates, ( b ) CV curves of P3HT/SWCNTs electrodes with different SWCNTs ratios at 50 mV s −1 and ( c ) CV curves of P3HT/50% SWCNTs at different scan rates .
…”
Section: Resultsmentioning
confidence: 79%
“…63 The scatter plots of reduced density gradient (RDG) versus the second largest eigenvalue of the Hessian matrix of electron density functions are obtained by Multiwfn 3.6 program. 64,65 composites contain low percentage of graphene, so a model should be such which corresponds to actual composite. Therefore, sandwich structures are considered where one or two oligothiophene chains are placed on either side of the graphene nanosheet or nanoribbon.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The composites with increasing concentration of graphene are also reported. 65 The concentration of graphene changes the optical properties of composites. The concentration of graphene is increased by using graphene nanoribbons containing 38, 46, and 54 carbon atoms.…”
Section: Interaction Energiesmentioning
confidence: 99%